Stress assessment instruments for hospitalized preterm newborns: scoping review - Mónica Costa; Maria Filomena Gaspar; Maria Alice Curado; Ana Brantes (BMC Nursing)
Abstract Background The highly technological environment existing in intensive care units, essential for the survival of the newborn, contributes with a potentially devastating and traumatic effect, especially in preterm newborns and in their future lives, due to the early and frequent exposure to multiple stressors. The preterm newborn must be observed in a systematic and structured way, before, during and after any intervention, aiming at the correct assessment and interpretation of his behaviour and signs of stress, and at the timely planning of interventions that minimize and prevent stress. The objective of this review is to identify and map the instruments for assessing stress in preterm newborns admitted to neonatal units in scientific evidence. Methods A scoping review was carried out using the methodology presented by The Joanna Briggs Institute (JBI) and the PRISMA ScR model (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extended for Scoping Reviews) for structuring the collected information. The research was carried out in three distinct phases supported by the Medline, CINALH databases through the EBSCO, Scielo and PubMed platform. Two reviewers screened all citations, abstract data and full-text articles, independently. Results Ten articles were selected, all primary studies. Seven different scales were identified in the studies. Discussion This review highlights the limited availability of instruments exclusively designed to assess neonatal stress in neonatology. While most tools, like the Newborn Comfort Behavior Scale and ALPS-Neo, focus on pain and stress together, the NISS and NSS provide valuable insights despite limitations in capturing individualized stress responses. Differentiating stress from pain is crucial for implementing targeted, neuroprotective interventions. Adapting neonatology environments and care practices to minimize stressors is essential for promoting newborns' well-being and long-term development. Conclusion The findings underscore the critical need for stress-specific assessment tools in NICUs to differentiate between pain and stress. Existing instruments offer valuable insights but have notable limitations. Expanding validated tools and prioritizing individualized, neuroprotective care are essential for improving outcomes. Adapting neonatology practices to reduce stressors and implement family-centered care will support the holistic needs of newborns, fostering their development, physiological stability, and overall well-being. System review registration Open Science Framework ( https://osf.io/nsu95/ ).